New JIT, new management technology principle - Amasaka, Kakuro 1947- (CRC Press, Taylor & Francis Group, 2015)
This book contains the previously published, updated, and new works of renowned scientist, scholar, and consultant Kakuro Amasaka. This book advances the Just-in-Time quality management strategy, bringing global readers into the cutting edge of a new management technology principle that surpasses what traditional JIT has accomplished. The new JIT principle contains hardware and software systems, and next generation technical principles for transforming management technology into management strategy. This comprehensive work covers traditional JIT, innovation and evolution, the full new JIT and its applications along with case studies